Success Factors of Smart Cities: A Systematic Review of Literature from 2000-2018 - Aldegheishem, Abdulaziz (TeMA - Journal of Land Use, Mobility and Environment, 2019)
The aim of this paper is to review smart city literature to achieve these goals. More than 150 sources of literature were approached and analyzed with a view of finding out drivers and success indicators of smart cities on which future research policies are depend. The results pointed out several drivers that stimulate cities to be smart. These drivers are related to economy, environment, governance, safety, energy, living, technology, buildings, education and people. Interestingly, a smart city should be distinguished by smartness extent achieved to meet the requirements of these drivers. That is, a smart city is the one that marked by its own smart economy, smart environment, smart governance, smart safety, smart energy, smart living, smart technology, smart buildings, smart education and smart people. This paper contributes to smart city literature by showing drivers and indicators related to smart cities success.